PENERAPAN KONSEP RUANG PUBLIK TERPADU RAMAH ANAK (RPTRA) PADA PERMUKIMAN STUDI KASUS : RPTRA GANDARIA SELATAN - MUHAMMAD SEGA SUFIA PURNAMA (LPPM, 2017)
Park is one of the important elements in the city. In Jakarta, it’s function not only for water reservoir but also as a space for gather, doing something together or just for fun. In this observation, researcher takes Friendly Child Integrated Public Space or Ruang Publik Terpadu Ramah Anak (RPTRA) as object of research. The novelty of this concept is imphasize of making a space for childern to play safely. Method used in this research is observation at the begining and continue with spread quisioner. The aim is to know the responds of citizen who lives arround the RPTRA and what are they suggest about it. The result is the existence of RPTRA can enhance the interest of citizen to come to RPTRA. This is because of many facilities not only for childern only but also for teenager and adult.